(NgIDROHIMIQ BOLOT (B:s ((NuRAL I pRIURALXE(B) /s - (N~ERNQEW(B, (NaLEKSANDR mIHAJLOWI^s; (NeREMEEWA(B, (NmUZA nIKOLAEWNAs ((NlENINGRAD (B:s (NgIDROMETEOIZDAT(B,s, 1989)
(NbIBLIOGR(B.: (NS(B. 416-423 (185 (NNAZW(B.)s
Keywords: (NbOLOTAs; (NgIDROHIMIQs; (NpRIURALXEs; (NuRALs